THE INFLUENCE OF REWARD SYSTEM ON EMPLOYEE JOB SATISFACTION WITH WORK MOTIVATION AS INTERVENING VARIABLES (Case Study on Employees of Medical Department United States) - Stephen Martinr; Martin Uribe (MEDALION JOURNAL: Medical Research, Nursing, Health and Midwife Participation, 2021)
This study aims to determine“The Influence of the Reward System on Employee Job Satisfaction with Work Motivation as an Intervening Variable (Case Study of Employees of Medical Department United States)